Toxic effects of vitamins and dietary supplements - Simic, Emilija; Marinovic, Dubravka; Stankovic, Veroslava; Dimitrijev, Igor (Education and Research in Health Sciences, 2023)
Vitamins and minerals are the most commonly used dietary supplements in the population worldwide. They play a key role in many cellular processes, including energy metabolism. They are used in case of deficit or to maintain adequate intake. In the absence of an underlying disease, long-term fatigue and lack of energy can be caused precisely by micronutrient deficits. Therefore, it is important to assess subclinical vitamin status and inadequate nutrition as potential risk factors for the occurrence of some diseases in apparently healthy individuals. The consumption of highly processed food is associated with an increase in chronic non-communicable diseases, due to the lower nutritional quality of the food. In addition to greater safety, better taste, and longer shelf life, certain food processing methods lead to the loss of minerals and vitamins. Furthermore, the bioavailability of vitamins can be hindered by various nutrients and dietary components. The need for supplementation exists especially in risk groups such as women and the elderly population. Due to the effect on the modulation of the immune response, vitamin supplementation during the COVID-19 pandemic proved to be justified especially in more severe forms of the disease as the disease course depended on the inflammatory response. However, toxic effects of vitamins and minerals have been documented in professional and scientific literature, so caution is required when using them. By reviewing the literature, this paper provides insight into the toxic effects of vitamins and dietary supplements from a medical, legal and social perspective. As a significant result, data supporting that supplements are used more and more frequently without a reason, without a doctor’s recommendation, in the absence of clinical manifestation of a deficit, and with scant knowledge of harmful effects, is highlighted. Based on this data, the paper presents proposals for measures to improve theory and practice.